NEW TECHNOLOGY IN EDUCATION: THE 4K MODEL AND WAYS OF ITS IMPLEMENTATION (Web of Teachers: Inderscience Research, 2025)
The article analyzes the main approaches to organizing the modern educational process. The role of the 4K model, its features, and application issues are examined.